Family presence during invasive procedures: a pilot study to test a tool - Eva de Mingo-Fernández; Ángel Belzunegui-Eraso; Guillermina Medina-Martín; Roser Cuesta-Martínez; Raquel Tejada-Musté; María Jiménez-Herrera (BMC, 2022)
Abstract Background Family Presence During Invasive Procedures (FPDI) generates controversy among healthcare professionals. Twibell and her team designed an instrument that measured nurses' Risk-Benefit and Self-Confidence perceptions regarding family presence during resuscitation and was used in numerous studies. Objectives Evaluate the new tool for Family Presence Risk-Benefit and Family Presence Self-Confidence during invasive procedures and find out the opinions of the medical and nursing staff on FPDIP. Method Cross-sectional methodological pilot study. Online and paper questionnaires modified from a previous translation. A factor analysis was performed for the validity of the indices and bivariate analysis for all the variables. Ethical approvals and research permissions were obtained according to national standards. Results One hundred twenty healthcare professionals (22.18%) answered the survey. Cronbach's α on the Family Presence Risk-Benefit scale was 0.877. Cronbach's α on the Family Presence Self-Confidence scale was 0.937. The correlation between the Risk-Benefit and Self-confidence variables is significant and with a moderate intensity of the relationship. A lower predisposition to Family Presence During Invasive Procedures is observed. Physicians are more reluctant than nurses. Conclusions The FPDI generates controversy as it alters health professionals' routines when they decide whether to allow it or not. There is a tendency for younger professionals to support FPDI. In general, health professionals, mainly physicians, do not favor FPDI. Health workers who perceive fewer risks and more benefits in FPDI and have greater self-confidence are more in favor of FPDI. The psychometric properties and internal consistency of the questionnaire indicate the validity and reliability of this tool.